(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
The present paper analyzes the emergence of fashion trends in Paris during the 1780s, whose self-proclaimed reference and inspiration came from the Orient. More fantasy and idealization of what the french conceived as oriental, these tendencies had little or no connection with what was used by the populations of the different localities and regions to which they referred, whether from Circasia, Turkey, China, Zion, Conchinchina or India. To this purpose, we examined the writings and illustrations of the magazines Cabinet des modes and Magasin des modes Nouvelles, along with reports in newspapers and anecdotaires from the period, in addition with memories of some well-known individuals of the late 18th century France. We do not see these trends as representations of a supposed “reality” of dress and clothing, but as objects that expose an intricate network of social exchange between the fashion sector that was being consolidated in Paris and political-diplomatic events and notions of exotic, sensual and unusual. The conclusion of the study is that the “orientalist” trends demonstrate the capacity of the Parisian fashion sector to assimilate current events and varied cultural elements into its operation. More than that, these trends emphasize the ability to use and dispose of cultural references, manipulate them for European tastes and needs and transform them into something completely new and that had little, if any, resemblance to the original inspiration and reality, even though they were widely publicized, sold and consumed as related to them.